Burn threshold prediction for high efficiency deep grinding - Bell, Andrew; Jin, T.; Stephenson, David J. (Elsevier, 2006)
Burn threshold diagrams are useful for the prediction of thermally induced grinding damage and were originally developed to describe the conventional shallow cut grinding regime. With the development of new high stock removal grinding processes such as High Efficiency Deep Grinding (HEDG), the prevention of thermal damage to the workpiece is of particular concern. The principle of HEDG is based around the change in thermal characteristics of the grinding process at high Peclet numbers, whereby less heat is partitioned to the workpiece. Conventional burn threshold diagrams are valid for Peclet numbers below 50, well below the values expected in HEDG. This study presents a modified approach to the construction of burn threshold diagrams which takes account of the change in thermal partitioning with Peclet number. The approach has been validated through grinding trials over a range of specific material removal rates.
Keywords: Grinding; High Efficiency Deep Grinding; HEDG; Burn threshold diagram